Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1038/labinvest.3700133
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of neutrophils and monocytes during subcutaneous plasma extravasation

Abstract: We examined the behavior of polymorphonuclear leukocytes (PMNs) and monocytes during subcutaneous plasma extravasation in guinea-pigs. Plasma extravasation was induced by intradermal injection of zymosanactivated plasma (ZAP). The degree of extravasation correlated logarithmically with the concentration of injected ZAP, and was composed of PMN-dependent and -independent components. The latter was mediated primarily by histamine. The former accounted for 40-50% of the total plasma extravasation, peaked within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Using a very different model system, Tokita and Yamamoto 15 recently reported that, upon intradermal injection into the skin of guinea-pigs, necrotic HL-60 cells enhanced local extravasation of plasma whereas apoptotic HL-60 cells had little or no effect. In the present study, we investigated the effects, on local vascular permeability (as assessed by 125 Ifibrinogen extravasation and 125 I-fibrin deposition), of the induction of apoptosis in native dermal MC populations whose numbers had been greatly expanded by the repetitive injection of the MC growth/ survival factor, SCF.…”
Section: Discussionmentioning
confidence: 99%
“…Using a very different model system, Tokita and Yamamoto 15 recently reported that, upon intradermal injection into the skin of guinea-pigs, necrotic HL-60 cells enhanced local extravasation of plasma whereas apoptotic HL-60 cells had little or no effect. In the present study, we investigated the effects, on local vascular permeability (as assessed by 125 Ifibrinogen extravasation and 125 I-fibrin deposition), of the induction of apoptosis in native dermal MC populations whose numbers had been greatly expanded by the repetitive injection of the MC growth/ survival factor, SCF.…”
Section: Discussionmentioning
confidence: 99%
“…Evans blue dye was used to measure vascular permeability enhancement (VPE) for 30 min (Supplemental Fig. 1) [32]. C5a/RP S19 exhibited the C5aR agonist-induced VPE at relatively high concentrations in comparison with C5a.…”
Section: C5ar Agonist-induced Histamine Release and Chemotaxis Of Hmcmentioning
confidence: 99%
“…injection of C5a was less marked in bone marrow failure patients [5] and in neutropenic patients [6]. We have demonstrated that PMN-dependent plasma extravasation is specific to PMN infiltration by showing that monocyte infiltration does not accompany plasma extravasation, even in the monocytotic state of peripheral circulation [7].…”
Section: Introductionmentioning
confidence: 68%
“…In terms of the mechanism of the PMN-dependent plasma extravasation, it was possible that the extravasation was simply a leakage of plasma during the passage of leukocytes at the postcapillary venule wall. However, we recently discarded this possibility when we observed that monocyte infiltration does not accompany plasma extravasation and that the PMN-dependent plasma extravasation occurs before PMN extravasation [7]. This strongly suggests the possibility that the PMN-dependent plasma extravasation is caused by a specific interaction between PMNs and endothelial cells.…”
Section: Introductionmentioning
confidence: 96%